Monetary Cooperation in East Asia: A Survey - Raul Fabella (Asian Development Bank (ADB), 2002)
"This paper surveys the growing literature on monetary cooperation in East Asia that goes beyond the Chiang Mai Initiative. It compares and contrasts the various proposals for cooperation such as the Williamson basket peg, the Asian monetary system, and the yen block as to their crisis prevention impact and their feasibility, both economic and political. The paper also reviews the evidence on the readiness of East Asia and some of its proper subsets for a currency union in the light of experiences elsewhere, especially of European monetary cooperation. On pure optimum currency area calculus alone, a case can be made for an East Asian currency union. But the great historical, developmental, political, and cultural diversity here highlighted stands as a formidable obstacle. Nonetheless, as the experience of Euroland shows, the very pursuit of even such a distant vision already brings benefits to participants."
hdl:11540/1927
Keywords: 330; Währungsunion; Internationales Währungssystem; Ostasien